2018
DOI: 10.1093/cid/ciy185
|View full text |Cite
|
Sign up to set email alerts
|

A Fungal Immunotherapeutic Vaccine (NDV-3A) for Treatment of Recurrent Vulvovaginal Candidiasis—A Phase 2 Randomized, Double-Blind, Placebo-Controlled Trial

Abstract: NCT01926028.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
102
0
7

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 140 publications
(120 citation statements)
references
References 23 publications
4
102
0
7
Order By: Relevance
“…This topical therapeutic approach works best when it follows an induction treatment phase with a fungicidal parenteral drug such as an echinocandin to prevent recurrence of candidiasis rather than being effective as treatment of acute severe oral or esophageal candidiasis. Novel antifungal agents with remarkable in vitro and in vivo activity against azole‐susceptible and ‐resistant Candida strains require future investigation in APECED patients with severe azole‐resistant CMC, as does the Als3‐based fungal vaccine that boosts IL‐17‐mediated anti‐ Candida immunity and is the first fungal vaccine shown to display efficacy in humans . Routine screening for gastrointestinal cancers is a recommended practice for all patients.…”
Section: Management Of Apeced Patientsmentioning
confidence: 99%
“…This topical therapeutic approach works best when it follows an induction treatment phase with a fungicidal parenteral drug such as an echinocandin to prevent recurrence of candidiasis rather than being effective as treatment of acute severe oral or esophageal candidiasis. Novel antifungal agents with remarkable in vitro and in vivo activity against azole‐susceptible and ‐resistant Candida strains require future investigation in APECED patients with severe azole‐resistant CMC, as does the Als3‐based fungal vaccine that boosts IL‐17‐mediated anti‐ Candida immunity and is the first fungal vaccine shown to display efficacy in humans . Routine screening for gastrointestinal cancers is a recommended practice for all patients.…”
Section: Management Of Apeced Patientsmentioning
confidence: 99%
“…This calls for a new and a more effective version of these vaccines. 24,[27][28][29][30][31][32] This study aims to introduce a new possible vaccine for C. albicans through analyzing peptides of its pyruvate kinase (PK) protein as an immunogenic stimulant computationally. Vaccine production that depends on biochemical experiments can be expensive, time consuming, hazardous and more likely to give unsatisfactory results, that's why bioinformatics approaches provide more affordable, efficient and faster techniques for vaccine development.…”
Section: Introductionmentioning
confidence: 99%
“…Als3p is also required for iron uptake from the host 10 . Our group has used Als3p for the development of an antiCandida funga vaccinel called NDV-3A 11 . NDV-3, containing a His-tagged recombinant version of the C. albicans Als3 protein N-terminus (rAls3p-N), formulated with alum, prevents both mucosal and hematogenously disseminated candidiasis in mice [12][13][14][15] .…”
Section: Introductionmentioning
confidence: 99%
“…NDV-3 was highly immunogenic, well-tolerated and had minimal minor side effects in a Phase I clinical trial 16 . Furthermore, the latest version of the vaccine, prepared with rAls3p-N without the His-tag, formulated with alum, (NDV-3A), was equally safe and immunogenic, and protective against vaginal infections, in an exploratory 1b/2a clinical trial of patients with a history of recurrent vulvovaginal candidiasis (RVVC) 11 . Subsequently, our group showed that serum antibodies from patients who responded to NDV-3A (but not those of the unresponsive patients) could prevent C.…”
Section: Introductionmentioning
confidence: 99%